Nanostructured Lipid Carrier Gel for the Dermal Application of Lidocaine: Comparison of Skin Penetration Testing Methods - Stella Zsikó; Kendra Cutcher; Anita Kovács; Mária Budai-Szűcs; Attila Gácsi; Gabriella Baki; Erzsébet Csányi; Szilvia Berkó (MDPI AG, 2019)
The aim of this research was to investigate the stability of a lidocaine-loaded nanostructured lipid carrier dispersion at different temperatures, formulate a nanostructured lipid carrier gel, and test the penetration profile of lidocaine from the nanostructured lipid carrier gel using different skin penetration modeling methods. The formulations were characterized by laser diffraction, rheological measurements and microscopic examinations. Various in vitro methods were used to study drug release, diffusion and penetration. Two types of vertical Franz diffusion cells with three different membranes, including cellulose, Strat-M®, and heat separated human epidermis were used and compared to the Skin-parallel artificial membrane permeability assay (PAMPA) method. Results indicated that the nanostructured lipid carrier dispersion had to be gelified as soon as possible for proper stability. Both the Skin-PAMPA model and Strat-M® membranes correlated favorably with heat separated human epidermis in this research, with the Strat-M® membranes sharing the most similar drug permeability profile to an ex vivo human skin model. Our experimental findings suggest that even when the best available in vitro experiment is selected for modeling human skin penetration to study nanostructured lipid carrier gel systems, relevant in vitro/in vivo correlation should be made to calculate the drug release/permeation in vivo. Future investigations in this field are still needed to demonstrate the influence of membranes and equipment from other classes on other drug candidates.